Current status of surgery-first approach (part III): the use of 3D technology and the implication in obstructive sleep apnea - Junho Jung; Seung-Hwan Moon; Yong-Dae Kwon (Maxillofacial Plastic and Reconstructive Surgery, 2020)
Abstract Considering psychosocial needs of patients, it is not surprising that surgery-first approach (SFA) is becoming more popular than ever. Although the concept of SFA was introduced a few decades ago, the limitation of analysis method based on two-dimensional images makes surgeons reluctant to choose SFA. Recently, the advancement of three-dimensional technology allows us to perform SFA even without minimal pre-surgical orthodontic treatment, and the prediction of surgical outcome became more accurate, especially in obstructive sleep apnea (OSA) patients to whom the advantages of SFA should be more significant. Here, we describe the current trend of SFA and its implication in OSA patients.